Influence of psychoactive use on self-perception of memory: an analysis during the SARS-CoV-2 pandemic (Research, Society and Development, 2022)
The present study aimed to verify the influence of psychoactive drug use on retrospective and prospective self-perception of memory during the SARS-CoV-2 pandemic. This is a cross-sectional, observational and analytical study conducted in 2020 with the Brazilian population. The research was carried out by filling out digital questionnaires containing questions related to sociodemographic data, knowledge related to the pandemic, use and frequency of psychoactive substances and the Prospective and Retrospective Memory Questionnaire (PRMQ-10) protocol. The results were analyzed using descriptive statistics and multiple linear regression, with a significance level of 5%. A total of 361 people participated, most females, with complete higher education, who did not belong to the group at risk for COVID-19 and who lived with people in this group. As for the frequency of use of psychoactive substances, most of the sample used it sporadically during the SARS-CoV-2 pandemic. The frequency of use of prescription and over-the-counter medications predicted the total PRMQ-10 score showing that the use of psychoactive substances used interfered with the self-perception of retrospective and prospective memory.